UJI BIOINFORMATIC MODELING SENYAWA AKTIF BIJI MELINJO (Gnetum gnemon L.) PADA PROTEIN KANKER SERVIKS DAN SARS COV-2 - Dhecella Winy Cintya Ningrum; Devi Rahmawati; Rifki Febriansah; Melany Ayu Octavia (Ikatan Senat Mahasiswa Farmasi Seluruh Indonesia, 2022)
Introduction: Cervical cancer cases in Indonesia are ranked second with the results ofdata in 2020 of 36,633 cases. During the COVID-19 pandemic, cancer patients aresusceptible to being infected by COVID-19. Study data from China, February 2020, therewere 107 cancer patients infected with COVID-19. It should get more attention becauseweakened immune form cancer patients. The purpose of this study was to determine thepotential of active compounds from melinjo seeds in inhibiting cervical cancer proteins andSARS CoV-2. Methods: The method used is bioinformatics test (STITCH -STRING) and moleculardocking test using Autodock Vina. The results will be seen from the lowest docking score.Result: The results of the bioinformatics test were obtained in the form of target proteinsfor cervical cancer regulators, namely MYC and TP53 (Resveratrol), FN1 and MAPK1(Gnetin C), SERPINE1 and VEGFA (Oleic Acid). The results from the analysis of thebinding affinity a target protein obtained the best binding affinity for cancer proteins, namelyGnetin C with FN1 with a docking score of -10.8 kcal/mol. The best affinity for SARS CoV2 protein after Remdesivir was for Resveratrol and Nsp3 with a docking score of -7.4kcal/mol. Conclusion: The results showed that the active compounds Resveratrol and Gnetin C hadgood potential in inhibiting cervical cancer protein and SARS CoV-2 with a lower dockingscore compared to the comparison drug Keywords: Gnetum gnemon L, bioinformatic modeling, cervical cancer, SARS CoV-2